An Introduction to Database Systems / Sixth Edition - Date C.J (Addison-Wesley Publishing Company, 1995)
The most comprehensive and up-to-date treatment of database technology currently available. Basic Concepts, An Introduction to Relational Database, The Relational Model, Relational Data Objects: Domains and Relations, The SQL Language, Database Design, Functional Dependencies, The Entity/ Relationship Model, Data Protection, Recovery, Concurrency, Security, Integrity, Further Topics, Views, Optimization, Missing Information, Object-Oriented Systems, Basic OO Concepts, Appendixes, Index.